2016
DOI: 10.1177/1758834016665077
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to therapy in estrogen receptor positive and human epidermal growth factor 2 positive breast cancers: progress with latest therapeutic strategies

Abstract: In this article, we focus on the subtype of estrogen receptor (ER)-positive, human epidermal growth factor 2 (HER2)-positive breast cancer (BC). Preclinical and clinical data indicate a complex molecular bidirectional crosstalk between the ER and HER2 pathways. This crosstalk probably constitutes one of the key mechanisms of drug resistance in this subclass of BC. Delaying or even reversing drug resistance seems possible by targeting pathways implicated in this crosstalk. High-risk patients currently receive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 97 publications
4
26
0
1
Order By: Relevance
“…Moreover, ER-negative (ER-) BC exhibited dismal survival rates due to the highly aggressive and metastatic behavior. However, how ER leads to uncontrolled cell proliferation of breast cancer is yet to be fully understood [27,28]. Moreover, few studies have focused on the dysregulation of lncRNAs in the ER-negative subtype breast cancer.…”
Section: Gse70947 Gse70947 Gse70947mentioning
confidence: 99%
“…Moreover, ER-negative (ER-) BC exhibited dismal survival rates due to the highly aggressive and metastatic behavior. However, how ER leads to uncontrolled cell proliferation of breast cancer is yet to be fully understood [27,28]. Moreover, few studies have focused on the dysregulation of lncRNAs in the ER-negative subtype breast cancer.…”
Section: Gse70947 Gse70947 Gse70947mentioning
confidence: 99%
“…The presence of hyperactive growth factor pathways increases ER transcriptional activities in a ligand-independent pattern, i.e., even in the presence of estrogen antagonism. [ 55 56 ]…”
Section: Mechanisms Of Resistance To Antiestrogen Therapymentioning
confidence: 99%
“…5c , purple), indicating that the performance of EL-NB and EL-B in C+T set relates to the molecular profile determining the response to the presence of trastuzumab in the treatment regimens. Moreover, since trastuzumab has been reported to be substantially less effective in oestrogen receptor (ER)-positive breast cancer 31 , 32 , it is important to note that the ER status of all cases enrolled in our study showed no correlation with the benefit from trastuzumab-containing therapy (Supplementary Fig. 5D , Supplementary Data 4 ).…”
Section: Resultsmentioning
confidence: 84%